1995
DOI: 10.1111/j.1365-2141.1995.tb05152.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal screening for fetal alloimmune thrombocytopenia: the results of a pilot study

Abstract: Feto-maternal incompatibility for the human platelet antigen HPA-1a is an important cause of severe fetal thrombocytopenia. The incidence is 1 in 1000-2000 pregnancies, which is more common than other conditions for which screening is presently carried out. Antenatal diagnosis and management are now available, but only for subsequent siblings following diagnosis of a previously affected infant. This study describes a pilot prospective screening programme for the antenatal detection of fetomaternal alloimmune t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 20 publications
6
39
1
Order By: Relevance
“…It is therefore essential to be able to diagnose these cases early to prevent complications. The detection rate of NAITP in the province of Quebec of 1 in 4100 found in our study is higher than the rate of 1 in 16,500 reported by Davoren and colleagues 31 in an observational study performed in Ireland, but lower than the rate reported in prospective trials 3,5 , 7,8 . Because of referral of all cases of PLT alloimmunization to a single central laboratory in Quebec, we are fairly confident that all investigated cases have been captured.…”
Section: Discussioncontrasting
confidence: 57%
“…It is therefore essential to be able to diagnose these cases early to prevent complications. The detection rate of NAITP in the province of Quebec of 1 in 4100 found in our study is higher than the rate of 1 in 16,500 reported by Davoren and colleagues 31 in an observational study performed in Ireland, but lower than the rate reported in prospective trials 3,5 , 7,8 . Because of referral of all cases of PLT alloimmunization to a single central laboratory in Quebec, we are fairly confident that all investigated cases have been captured.…”
Section: Discussioncontrasting
confidence: 57%
“…A large prospective study of 24,417 pregnancies in East Anglia identified and followed up 387 pregnancies in HPA‐1a negative women, and found that HPA‐1a antibodies developed in 46, equivalent to an incidence of HPA‐1a alloimmunisation of 1 in 350 unselected pregnancies (Williamson et al, 1998). The incidence of neonatal thrombocytopenia associated with alloimmunisation was 22/24,417 pregnancies (1 in 1,100) which is in agreement with previous smaller studies and some recent large surveys (range 1 in 600 to 1 in 5,000; mean 1 in 1446) (Table 1) (Mueller‐Eckhardt et al, 1985; Blanchette et al, 1990; Burrows and Kelton, 1993; Doughty et al, 1995; Dreyfus et al, 1997; Maslanka et al, 2002; Davoren et al, 2002; Husebekk et al, 2002; Bessos et al, 2002).…”
Section: The Conditionsupporting
confidence: 91%
“…The 6 prospective studies 24,25,28,29,31,32 in which platelet counts were obtained from the neonates immediately after delivery may reflect the natural history of NAIT better than the other prospective studies 7,8,[21][22][23]26,27,33,34 in which pregnant women were HPA 1a typed, because different interventions were employed in many of the latter studies. A comparison with the first group may therefore be more relevant in order to examine whether implementation of our screening and intervention program reduces the number of serious complications to severe NAIT.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the previously published prospective studies 8,[26][27][28][29]34 have used a more proactive strategy with FBS and intrauterine transfusions. We decided not to use such a strategy because of the increased risk of fetal death associated with FBS in pregnancies complicated by fetal thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%